Effects of free float on equity returns of shares listed on the JSE Securities Exchange . - Mokoena, Kabelo Lethlogonolo (My University, 2017)
Purpose: The purpose of this research is to analyse and examine the effects of free float on equity returns for JSE-listed shares with the aim of submitting empirical evidence to support the inclusion of free float assessment to the investment decision-making processes of equity investors. Design/Methodology/Approach: Monthly equity returns of FTSE/JSE All Share Index constituent companies were cross-sectionally regressed on the values of five firm characteristics from November 2003 through to the end of December 2015 using Ordinary Least Squares (“OLS”) Cross-Sectional Regressions (“CSR”). The research followed the line of thought of and built on the work of Auret and Sinclaire (2006) by adopting a similar asset pricing research approach/methodology whilst introducing the free float as a firm attribute for explaining variations in equity returns. Four other firm characteristics already identified from the works of van Rensburg and Robertson (2003), Auret and Sinclaire (2006), Thomson and Reddy (2013), and Hodnett, Hsieh, and van Rensburg (2012) are also assessed alongside the free float. Findings: The main finding of the study was that free float has the capacity to explain some of the variations in equity returns. The combination of free float and earnings yield ratio displayed stronger explanatory power for variations in equity returns than the van Rensburg and Robertson (2003) size-P/E returns model. Implications: Investment decision-making processes of listed equity investors ought to consider the free float of investee companies as part of their assessment process. Not only does the free float give a truer picture of the investable universe of listed companies (Ideo, 2001), free float is also said to influence a number of important performance aspects such as share liquidity, information flow, price volatility, corporate governance, trading activity, firm valuation, and management decision-making (Alzeaideen and Al-Rawash iii (2014). Consequently, failure to appraise the free float could be oblivious and detrimental to the investment objectives. Originality/Value: The influx of empirical evidence exposing the inept of the capital asset pricing model in explain equity return variations (Hodnett et al., 2012) has triggered the evolution of a new strand in asset pricing research seeking to uncover firm-specific attributes able to generate alpha/above-market returns (Thomson & Reddy, 2013). This study contributes to this new strand in asset pricing research by submitting the free float as a candidate firm attribute for explaining variations in equity returns. Despite the increase in studies devoted towards identifying firm-specific attributes influencing equity return variations (Thomson & Reddy, 2013), the literature review of this study discovered scant coverage of the free float in asset pricing research (Chan, Chan, & Fong, 2004). In particular to the JSE, at the time of writing, the literature review had not identified any published academic journal appraising the effects of or discussing the economic theory pertaining to free float. Key words and phrases: Free float, equity returns, JSE Securities Exchange, asset pricing, capital markets, liquidity .
MBA Thesis
Keywords: Free float, equity returns, JSE Securities Exchange, asset pricing, capital markets, liquidity